2023
DOI: 10.3390/su15086524
|View full text |Cite
|
Sign up to set email alerts
|

The Nexus between Managerial Overconfidence, Corporate Innovation, and Institutional Effectiveness

Abstract: Innovative projects are considered risky and challenging, and specific managerial traits (such as managerial overconfidence) are needed to gain momentum. Moreover, corporate innovations are also crucial for sustainable development through the creation of more efficient, ecofriendly, and socially responsible products, processes, and business models. Therefore, the present study adds to the existing literature by examining (a) how managerial overconfidence influences firm-level innovation, (b) whether the streng… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 105 publications
0
0
0
Order By: Relevance
“…Previous research has indicated that both established multinational firms and small start-ups can benefit from the external network of relationships that top managers have [38] . For example, at McDonald's, the CEO actively used external information to promote internal organizational change, making the firm more responsive to strategic changes brought about by different contexts and competitive pressures.…”
Section: Establishing New Social Tiesmentioning
confidence: 99%
“…Previous research has indicated that both established multinational firms and small start-ups can benefit from the external network of relationships that top managers have [38] . For example, at McDonald's, the CEO actively used external information to promote internal organizational change, making the firm more responsive to strategic changes brought about by different contexts and competitive pressures.…”
Section: Establishing New Social Tiesmentioning
confidence: 99%